Dorsoventral Patterning in Hemichordates: Insights into Early Chordate Evolution - Lowe, Christopher J; Terasaki, Mark; Wu, Michael; Freeman, Robert M, Jr.; Runft, Linda; Kwan, Kristen; Haigo, Saori; Aronowicz, Jochanan; Lander, Eric; Gruber, Chris; Smith, Mark; Kirschner, Marc; et al. (PLOS Biology, 2006)
Experimental and anatomical evidence for the role of Bmp and Chordin in the development of the dorsal-ventral axis of hemichordates provides insights into the evolution of the chordate lineage.